Bruno Latour and Niklas Luhmann as organization theorists. Issue 2 (April 2017) - Czarniawska, Barbara
Abstract: Bruno Latour and Niklas Luhmann are two authors who, not being management and organization scholars, have had a significant impact on MOS studies. Their works are even more appreciated in time, yet their influence has not crossed the Atlantic. The texts of the two authors, and the predecessor they evoke, demarcate a truly European development of management and organization theory.